Access to second-line drug susceptibility testing results among patients with Rifampicin resistant tuberculosis after introduction of the Hain® Line Probe Assay in Southern provinces, Zimbabwe. (April 2019) - Timire, Collins; Sandy, Charles; Kumar, Ajay M.V.; Ngwenya, Mkhokheli; Murwira, Barbara; Takarinda, Kudakwashe C.; Harries, Anthony D.
Highlights: 95% of patients started a standard MDR-TB regimen while 6(5%) had pre-treatment attrition. 91% of the patients were initiated on treatment within a week. Only 40% of second-line DST (SL-DST) results were received by requesting facilities. The standard MDR-TB regimen was a suboptimal therapy in 9 (13.2%) of the patients since they had resistance to fluoroquinolones. Patients in facilities >250 km from the reference laboratory get SL-DSTs after 79 days! Abstract: Objectives: To determine the proportion of rifampicin-resistant tuberculosis (RR-TB) patients who accessed second-line drug susceptibility testing (SL-DST) results following introduction of the Hain technology in southern provinces, Zimbabwe. Design: Cohort study using secondary data. Results: Xpert MTB/RIF results were used to identify 133 RR-TB patients for this study. Their mean age (SD) was 37.9 (11.1) years, 83 (62%) were males and 106 (80%) were HIV-infected. There were 6 (5%) participants who had pre-treatment attrition. Of the 133 pulmonary TB (PTB) patients, 117 (80%) had additional sputum specimens collected; 96 (72%) specimens reached the National TB Reference Laboratory (NTBRL); 95 (71%) were processed; 68 (51%) had SL-DST results. Only 53 (40%) SL-DST results reached the peripheral facilities. Median time from specimen reception at the NTBRL to SL-DSTs was 40 days, interquartile range (IQR: 28–67). Median time from presumptive diagnosis of RR-TB by health care worker to SL-DST results was 50 days (IQR: 39–80), and increased to 79 days (IQR: 39–101) in facilities >250 km from the NTBRL. The proportion with any fluoroquinolone resistance was 9 (13.2%). Conclusion: Although RR-TB patients with PTB were initiated timely on treatment, access to SL-DSTs by facilities needs improvement. Health inequities exist as remote areas are less likely to get SL-DST results in time.